f(0, 1,

h(0,

g(

g(

R

↳Dependency Pair Analysis

F(0, 1,X) -> H(X,X)

H(0,X) -> F(0,X,X)

Furthermore,

R

↳DPs

→DP Problem 1

↳Non Termination

**H(0, X) -> F(0, X, X)**

f(0, 1,X) -> h(X,X)

h(0,X) -> f(0,X,X)

g(X,Y) ->X

g(X,Y) ->Y

Found an infinite P-chain over R:

P =

H(0,X) -> F(0,X,X)

F(0, 1,X) -> H(X,X)

R =

f(0, 1,X) -> h(X,X)

h(0,X) -> f(0,X,X)

g(X,Y) ->X

g(X,Y) ->Y

s = F(0, g(1, 0), g(1, 0))

evaluates to t =F(0, g(1, 0), g(1, 0))

Thus, s starts an infinite chain.

Duration:

0:00 minutes